PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG PERPUSTAKAAN PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI KALIMANTAN TIMUR - Ida Rahmawati3, Jayanti Riana Putri1, Eka Yudhyani2, (EKONOMIA, 2021)
The purposes of this research was determine the effect of each indicators of tangibles, reliability, responsiveness, assurance, and empathy on the satisfaction of library visitors either partially or simultaneously.This research was conducted in the library of the East Kalimantan Regional Development Planning Agency (Bappeda) office, on Kesuma Bangsa Street Number 2 Samarinda which is located on the 2nd floor of the PUSIDO building area of the East Kalimantan Province Bappeda office. The method used in this research is descriptive research method through a quantitative approach using multiple linear regression analysis tools. The research data source is primary data through distributing questionnaires to 87 respondents of visitors to the library of Bappeda East Kalimantan Province.The results of the analysis and calculations show the effect of service quality partially with indicators of tangibles, reliability, assurance has a positive and insignificant effect, responsiveness has a significant positive effect, and empathy has a negative and insignificant effect on visitor satisfaction at the Bappeda library of East Kalimantan Province.Simultaneously, the five service indicators have a significant positive effect on visitor satisfaction at the Bappeda library of East Kalimantan Provinc